Aglomerado estelar M67: processos de diluição e a evolução do Momentum Angular - Martins, Bruno Leonardo Canto (2007)
Galactic stellar clusters have a great variety of physical properties that make valuable probes of stellar and galactic chemical evolution. Current studies show a discrepancy between the standard evolutionary models and observations, mainly considering the level of mixing and convective dilution of light elements, as well as to the evolution of the angular momentum. In order to better settle some of these properties, we present a detailed spectroscopic analysis of 28 evolved stars, from the turn-off to the RGB, belonging to the stellar open cluster M67. The observations were performed using UVES+FLAMES at VLT/UT2. We determined stellar parameters and metallicity from LTE analysis of Fe I and Fe II lines between 420 1100 nm. The Li abundance was obtained using the line at 6707.78 ˚A, for the whole sample of stars. The Li abundances of evolved stars of M67 present a gradual decreasing when decreasing the effective temperature. The Li dilution factor for giant stars of M67 with Teff ∼ 4350K is at least 2300 times greater than that predicted by standard theory for single field giant stars. The Li abundance as a function of rotation exhibits a good correlation for evolved stars of M67, with a much smaller dispersion than the field evolved stars. The mass and the age seem to be some of the parameters that influence this connection. We discovered a Li-rich subgiant star in M67 (S1242). It is member of a spectroscopic binary system with a high eccentricity. Its Li abundance is 2.7, the highest Li content ever measured for an evolved star in M67. Two possibilities could explain this anomalous Li content: (i) preservation of the Li at the post turn off stage due to tidal effects, or (ii) an efficient dredge-up of Li, hidden below the convective zone by atomic diffusion occurring in the post turn off stage. We also study the evolution of the angular momentum for the evolved stars in M67. The results are in agreement with previous studies dedicated to evolved stars of this cluster, where stars in the same region of the CM-diagram have quite similar rotations, but with values that indicate an extra breaking along the main sequence. Finally, we analize the distributions of the average rotational velocity and of the average Li abundance as a function of age. With relation to the average Li abundances, stars in clusters and field stars present the same type of exponencial decay law t−β. Such decay is observed for ages lesser than 2 Gyr. From this age, is observed that the average Li abundance remain constant, differently of the one observed in the rotation age connection, where the average rotational velocity decreases slowly with age